PREGABALIN EFFECTS ON CELLULAR AND HUMORAL COMPONENTS OF BLOOD OF MICE (Mus musculus) - Wissam Sajid Hashim Al-Uboody (Basrah Journal of Veterinary Research)
The oral use of pregabalin was evaluated in this study to reveal its effects on some hematological and biochemical parameters of laboratory mice. The animals of this study were divided into three groups (twelve mice each). The control group was fed on a standard ration. The first treated group (Pregabalin 1) were dosed orally with one ml of distilled water containing Pregabalin (20 mg/ml/mice/ day). The second treated group (Pregabalin 2) were dosed orally with one ml of distilled water containing pregabalin (40mg/ml/mice/ day). The experiment continued for two successive months. The results showed that the use of pregabalin caused a significant declination in R.B.C., HGB, HCT, W.B.C., M.C.V., MCH, and MCHC of both treated groups compared them with control group and the declination was more significant in (pregabalin 2) group compared with (pregabalin 1) group. The RDW-CV, RDW-SD, and PLT increased significantly in both treated groups as compared with those of the control group. However, PCT, PDW and MPV were not affected by the use of pregabalin except the MPV of (Pregabalin 2) group was significantly less than that of (Pregabalin 1) but without a significant difference compared with that of control. The Fe++, and GLU decreased significantly in both treated groups compared with the control and they declined more significantly in (Pregabalin 2) compared with (Pregabalin 1). Both the TP and Ca++ did not affected by the use of pregabalin compared with the control group (P≤0.05)